Effects of phosphorus and potassium levels on the yield of the tuber variety criolla colombia in the department of cundinamarca (2011)
In the locations of Zipaquirá and Cogua located in the department of Cundinamarca, the effects of applying different levels of phosphorus and potassium on tuber yield and specific gravity in the diploid potato variety Criolla Colombia were evaluated. The design used a completely randomized block with three replications and a 4 x 4 factorial structure, where the first factor corresponds to phosphorus (0, 50, 100 and 150 kg ha-1 P2O5), and the second, potassium (0, 50, 100 and 150 kg ha-1 k2O). The variables evaluated were specific gravity and tuber yield in the categories: first (PT1), second (PT2), third (PT3) and total (PTT). In Zipaquirá, there were differences in the phosphorus factor for the yield variables PT1, PT2 and PTT, while in the town of Cogua, the only difference for this factor was found in the variable PTT. In these variables, the levels of 50, 100 and 150 kg ha-1 of P2O5 produced higher yields that were equal and above that of the 0 kg ha-1 P2O5 level. In the potassium factor, differences were found only for the yield variable PT3 in the town of Cogua. The specific gravity did not respond to the P or K factors evaluated.